Mitochondrial dysfunction and potential anticancer therapy. Issue 6 (6th July 2017) - Lleonart, Matilde E.; Grodzicki, Robert; Graifer, Dmitri M.; Lyakhovich, Alex
Abstract: Mitochondrial dysfunction (MDF) has been identified as an important factor in various diseases ranging from neurological disorders, to diseases of the cardiovascular system and metabolic syndromes. MDF was also found in cancer as well as in cancer predisposition syndromes with defective DNA damage response (DDR) machinery. Moreover, a recent highlight arises from the detection of MDF in eukaryotic cells upon treatment with antibiotics. In this review, we focus on recent studies of MDF in pathological conditions with a particular emphasis on the effects of various classes of antibiotics on mitochondria. Special attention is given to the role of autophagy/mitophagy in MDF and repurposing antibiotics as anticancer drugs.